(untitled) (Intent Research Scientific Journal, 2025)
The quality of soil cultivation with traditional plows does not meet agrotechnical requirements. The goal of the research is to develop a plow for smooth, furrowless plowing. A plow for smooth plowing is proposed, which contains double screw bodies, pushers of the first row, rear screw right- and left-turning plow bodies, pushers of the second row. An experimental model of a plow for smooth plowing was manufactured. The results of field tests of the developed plow are presented. It has been established that the quality indicators of the plow fully comply with agrotechnical requirements. At the same time, the degree of reduction in fuel consumption compared to the existing plow is 21.26%.